Implementation of holographic displays to increase realism in virtual reality through 3D images that simulate being in the environment - Álvarez Esquivel, Diego Arturo (2024)
This paper presents a study on the use of holographic displays in virtual reality. It highlights the significant advances that virtual reality has experienced in recent years and emphasizes the importance of improving realism in the immersive experience. The potential of holographic displays to enhance the quality of virtual reality by generating 3D images that resemble real physical objects is discussed. The current limitations of electro holographic recording due to the pixelated structures used are mentioned. A model for generating digital holograms using holographic displays is described, based on image superposition techniques and convolution with a point spread function. It is concluded that holographic displays have the potential to revolutionize virtual reality by providing high-quality 3D images and increased interactivity.